Improving Reading Skills Through a Classroom Literacy Program: A Case Study at SMPN 1 Balaraja - Putri, Wafa Aulia; Rohim, Abdul; Anggraini, Diah Retno (Universitas Jambi, Magister Program of English Education Department, 2026)
Reading literacy continues to represent a significant educational challenge among junior high school students. This study investigates the implementation and effectiveness of a classroom literacy program in enhancing students’ reading skills at SMPN 1 Balaraja. A qualitative approach with a case study design was employed. The participants consisted of 15 seventh-grade students selected through purposive sampling and two English teachers as key informants. Data were collected through classroom observations, semi-structured interviews, documentation, and reading tests. The research instruments were developed based on classroom literacy indicators and validated by two English education experts. Data analysis followed Miles and Huberman’s interactive model, encompassing data reduction, data display, and conclusion drawing, supported by descriptive analysis of students reading test results. The findings indicate that the classroom literacy program has been implemented consistently and institutionally across grade levels in line with the Independent Curriculum. The program contributes positively to students vocabulary development, pronunciation, and overall reading ability. However, its effectiveness is constrained by students low learning motivation, limited English proficiency, and insufficient support from family and community environments. In conclusion, the study suggests that classroom literacy programs can enhance students reading skills when supported by continuous pedagogical guidance and strong collaboration among schools, families, and the wider community.